Juridical Study of Reforming the Criminal Procedural Law System regarding Pretrial Institutions after Constitutional Court Decision in Indonesia - Nurbaedah Nurbaedah (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
This study examines the problem of reforming the criminal procedural law system regarding pretrial institutions in Indonesia after the decision of the Constitutional Court No. 21/PUU-XII/2014. The purpose of this study is to analyze in an effort to reform the criminal procedural law system regarding pretrial institutions in Indonesia. This research method uses normative legal research. The results of this study describe that the changes in the Criminal Procedure Law System Regarding Pretrial Institutions in Indonesia after the Constitutional Court Decision No. 21/PUU-XII/2014 are the scope of pretrial examination is not only limited to whether or not an arrest, detention, termination of investigation or termination of prosecution is legal; compensation and or rehabilitation for a person whose criminal case is terminated at the level of investigation or prosecution; whether or not the determination of a suspect, confiscation and search is valid, but also has the authority to test whether the investigation is legal or not, in the case that the case being investigated has ne bis in idem elements, the case being investigated has an error in persona, the case being investigated is strongly suspected of being a criminalization. Examination material in pretrial cases is not only on procedural law enforcement actions, but can enter case material so that a simple, fast, and low-cost trial can be well integrated in the criminal procedural law system. The pretrial institution as a control function can concretely guarantee the balance of rights of Indonesian citizens who are in contact with criminal cases, both as investigators, witnesses, and suspects.